(untitled) (Research, Society and Development, 2021)
Introduction: Videolaparoscopic surgery is a minimally invasive surgical method of the abdomen and its internal organs, performed through a camera connected through the abdominal wall using forceps by the surgeon. The most common surgeries by laparoscopy are: bariatric, gynecological, treatment of abdominal hernias, among others. Objective: To show the advantages and disadvantages of videolaparoscopic surgery and to study the advances in relation to new techniques used in medicine in relation to surgery. Method: This is a descriptive research of the integrative literature review type, which seeks to report the positive and negative points of videolaparoscopic surgery in relation to laparotomy. The search was carried out using PubMed MEDLINE databases, Scientific Electronic Library Online (Scielo), Cochrane Library, Google Scholar, LILACS and Academic Google, during the months of July and August 2021. Thus, a total of 29 productions were made. for an integrative literature review. Results: Considering the surgical procedures involving laparoscopy and laparotomy, it is possible to see greater benefits in the first procedure, such as faster hospital discharge due to the minimally invasive incision that this allows. Conclusion: Videolaparoscopy is a modern and less invasive procedure, used as an alternative to laparotomy, having advantages such as shorter surgical time, reduced complications and morbidity and mortality and a better aesthetic result of healing, but also disadvantages such as damage to organs and vessels, herniation or decrease in residual lung capacity. Therefore, laparotomy is more necessary in patients with cardiac and pulmonary risks.